A ferrocene functionalized rotaxane host system capable of the electrochemical recognition of chloride. - Evans, N; Beer, P (2011)
A ferrocene appended rotaxane is prepared by chloride anion templation and ring closing metathesis. Upon removal of the chloride template, the rotaxane is demonstrated to be selective for chloride over more basic oxoanions by (1)H NMR spectroscopy and electrochemistry, in marked contrast to an acyclic analogue--the first example of a solution based redox-active interlocked host system capable of the electrochemical recognition of anions.